"From Rote Memorization to Self-Directed Learning: A Longitudinal Study of Montessori’s Impact on EFL Motivation in Uzbek Adolescents" (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study investigates the effectiveness of the Montessori method in enhancing motivation and English language proficiency among Uzbek high school students, contrasting it with traditional rote memorization approaches. Conducted over two academic years (2022–2024) in Tashkent, the research employed a mixed-methods design involving 60 students (30 Montessori, 30 control). Quantitative data from motivation surveys (AMS) and CEFR-aligned language tests, alongside qualitative insights from interviews and classroom observations, revealed that Montessori students exhibited a 35% increase in intrinsic motivation and a 22% improvement in speaking skills. Challenges included curriculum misalignment and resource scarcity. The findings advocate for integrating Montessori principles into Uzbekistan’s educational reforms to foster psychological autonomy and global competence.